2012
DOI: 10.1111/j.1476-5829.2012.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of oral docetaxel and cyclosporine in canine epithelial cancer

Abstract: The goal of the current study was to determine the efficacy of oral docetaxel in combination with cyclosporine in the treatment of canine epithelial cancer. Requirements for eligibility were histological confirmation of epithelial neoplasia, measurable disease, no chemotherapy treatment within 2 weeks, and a life expectancy of ≥ 3 months. Fifty-one dogs were enrolled. All dogs received 1.625 mg kg(-1) of docetaxel with 5 mg kg(-1) of cyclosporine (DT/CSA) by gavage. Ten dogs had progressive disease at 2 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Of particular note, PCA cell lines did not appear to be more sensitive to docetaxel compared to iUC cell lines. These cell culture findings are not incongruent with recently described activity of docetaxel in dogs with epithelial malignancies [ 46 ]. In this phase II study, 51 dogs were treated with docetaxel with an objective response rate of 16.7% (8/48 partial responses), however only ~ 20% of the evaluated patient population had uroepithelial carcinomas (8 bladder and 2 prostate) and clinical response rates were not different between these 2 limited subpopulations.…”
Section: Discussionsupporting
confidence: 85%
“…Of particular note, PCA cell lines did not appear to be more sensitive to docetaxel compared to iUC cell lines. These cell culture findings are not incongruent with recently described activity of docetaxel in dogs with epithelial malignancies [ 46 ]. In this phase II study, 51 dogs were treated with docetaxel with an objective response rate of 16.7% (8/48 partial responses), however only ~ 20% of the evaluated patient population had uroepithelial carcinomas (8 bladder and 2 prostate) and clinical response rates were not different between these 2 limited subpopulations.…”
Section: Discussionsupporting
confidence: 85%
“…A phase II study to determine the efficacy of oral docetaxel in the management of canine epithelial tumors has been completed. In this study canine oral squamous cell carcinoma was found to be responsive to oral docetaxel [36]. Furthermore a phase II study to determine the efficacy of oral docetaxel in the management of feline epithelial tumors targeting oral squamous cell carcinoma is currently ongoing.…”
Section: Introductionmentioning
confidence: 95%